The Application of Thought Stopping (TS) / Stopping Negative Thinking and Assertive Trainning (AT) / Assertive Behavior to Drug Abusers in Class II A Correctional Institutions Pekanbaru - Usraleli Usraleli (Universitas Lancang Kuning, 2022)
The main problem with Correctional Institutions is the overcrowded experienced by most prisons in Indonesia. Of the total 33 regional offices in Indonesia, only 8 regional offices were not overcrowded, 5 (five) of which were North Sumatra, Riau Islands, Riau, Jambi and Bengkulu. The impact of overcrowded is that it will be very difficult to carry out an effective and efficient coaching. Triggers various problems, including: drug trafficking, friction that occurs between residents, fighting over food, beds, bathrooms, and many other things that trigger quarrels and fights because of each other's taunts or stealing food (Wilson, 2005 and Hensly . et al, 2003 in Mahnun Lailan Nasution, 2015). In such a condition, efforts should be made so that the assisted residents respect each other and undergo good guidance in prison, namely through Thought Stopping and Assertive Trainning. The purpose of this community service is to know how to implement Tought Stopping (TS) / stop negative thoughts and Assertive Trainning (AT) / assertive behavior of Assisted Citizens with drug abuse in Class II A Correctional Institutions Pekanbaru. This community service activity was carried out from September to December 2020 at the Class II A Correctional Institution Pekanbaru, North Tangkerang Village, Bukit Raya subdistrict, Pekanbaru City. This service activity is in the form of training to stop negative thoughts and behave assertively to the assisted residents. PkM's target audience is 25 assisted citizens. This activity begins with the implementation of correct assertive training and then the thought stopping of the assisted residents is trained. The techniques for implementing thought stopping and assertive training are describing, modeling, role playing, feedback, transferring. The output of this PkM activity is a scientific article published in an accredited national community service journal. The target achievement is that the assisted residents are able to decide negative thoughts and be able to behave assertively.